CARBONATES IN CM2 CHONDRITES: CONSTRAINTS ON ALTERATION CONDITIONS FROM OXYGEN ISOTOPIC COMPOSITIONS AND PETROGRAPHIC OBSERVATIONS - Benedix G.K.; Leshin L.A.; Farquhar J.; Jackson T.; Thiemens M.H. (My University, 2003)
High-precision measurements of the oxygen isotopic compositions of carbonates (calcite and dolomite) from five CM2 chondrites are presented and put into context of the previously determined mineralogic alteration index (MAI), which places these meteorites into an alteration sequence. The carbonate oxygen isotopic compositions range from +20.0 to +35.7%% for δ18O, +8.0 to +17.7%% for δ17O, and -0.7 to -2.7%% for Δ17O. Carbonate Δ17O values are inversely correlated with MAI and track the evolution of fluid composition from higher to lower Δ17O values with increasing alteration on the CM parent body. Similar Δ17O values for calcite and dolomite fractions from the same splits of the same meteorites indicate that calcite and dolomite in each split precipitated from a single fluid reservoir. However, reversed calcite dolomite fractionations (δ18Odol - δ18Occ) indicate that the fluid was subject to processes, such as freeze-thaw or evaporation, that fractionated isotopes in a mass-dependent way. Consideration of the carbonate isotopic data in the context of previously proposed models for aqueous alteration of carbonaceous chondrites has provided important insights into both the evolving alteration conditions and the utility of the models themselves. The data as a whole indicate that the isotopic evolution of the fluid was similar to that predicted by the closed-system, two-reservoir models, but that a slightly larger matrix-water fractionation factor may apply. In the context of this model, more altered samples largely reflect greater reaction progress and thus probably indicate more extended times of fluid exposure. Petrographic observations of carbonates reveal a trend of variable carbonate morphology correlated with alteration that is also consistent with changes in the duration of fluid-rock interaction. The data can also be reconciled with fluid-flow models in a restricted region of the parent body, which is consistent with assertions that the different types of carbonaceous chondrites derive from different regions of their parent bodies. In this case, the model results for a 9-km-radius body, and our data place the location of the CM chondrite formation in a 100-m-thick zone 1 km from the surface. The size of this zone could be increased if the model parameters were adjusted.